Pathological complete response following neoadjuvant chemotherapy for locally advanced intrahepatic cholangiocarcinoma - Yoshitaka Shimamaki; Isamu Hosokawa; Tsukasa Takayashiki; Shigetsugu Takano; Itaru Sonoda; Masayuki Ohtsuka (Surgical Case Reports)
Abstract Background Intrahepatic cholangiocarcinoma (ICC) is the second most common primary liver cancer. Cases when found are often advanced with vascular invasion, and radical resection is often difficult. Despite curative resection, the postoperative recurrence rate of patients with histological lymph node metastasis is high, and their prognosis is poor. Therefore, there is an urgent need to establish multidisciplinary treatment that combines chemotherapy and surgical resection. The efficacy of neoadjuvant chemotherapy (NAC) for locally advanced ICC is unclear. In this report, a case of locally advanced ICC in which pathological complete response (pCR) was achieved after NAC is described. Case presentation A 79-year-old woman was admitted to a local hospital with appetite loss. Computed tomography showed a 100 × 90 mm low-contrast tumor in the left hepatic lobe and segment 1 with invasion to the inferior vena cava (IVC), and several lymph nodes along the left gastric artery and lesser curvature were enlarged. Therefore, she was treated with a combined chemotherapy regimen of gemcitabine and cisplatin. After four courses, the tumor size decreased to 30 × 60 mm without invasion to the IVC. Left hepatectomy extending to segment 1 with bile duct resection combined with middle hepatic vein resection (H1234-B-MHV), dissection of regional lymph nodes and pyloroplasty were performed. After radical resection, pCR was achieved. She is alive with no evidence of disease, 2 years after surgery. Conclusions In this case, a patient with locally advanced ICC achieved pCR to NAC. NAC may be effective for ICC. Patients who achieve pCR may have a better prognosis.